2021
DOI: 10.2478/rtuect-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy Retrofit Assessment Methodologies in Buildings by European Research Projects

Abstract: Energy retrofit of existing buildings is one of the main keys to achieve European Union’s decarbonising objectives defined in the European Green Deal. In order to proceed into them, European policy has been adapted and several research projects are developed. The aim of this paper is to analyse the assessment methodology of the research projects, setting up the overview of the assessed fields and the criteria followed to perform and evaluate each project. As working methodology, 18 projects have been studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Also another challenge in implementing the European Green Deal is seen in the diversity and division among the member states regarding the climate policies (Haas & Sanders, 2020;Dupont & Torney, 2021). The objectives, measures, and policies implied by the European Green Deal concern several aspects already researched by academics, such as agriculture (Montanarella & Panagos, 2021;Bartolome et al, 2022), building refurbishments (Pohoryles et al, 2020Napoli et al, 2020;Arbulu et al, 2021;Buckley et al, 2021;Loli & Bertolin, 2021), technology (Hainsch et al, 2021), transport (Hass & Sander, 2020, urban tourism (Popescu et al, 2022), regional development (Piontek, 2020) and economic recovery (García Vaquero et al, 2021;Kougias et al, 2021;Bongardt & Torres, 2022), etc. Building refurbishments, as a way to reduce greenhouse gas emissions and to reduce resources consumptions for heating, triggered our attention towards renovating residential flats.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also another challenge in implementing the European Green Deal is seen in the diversity and division among the member states regarding the climate policies (Haas & Sanders, 2020;Dupont & Torney, 2021). The objectives, measures, and policies implied by the European Green Deal concern several aspects already researched by academics, such as agriculture (Montanarella & Panagos, 2021;Bartolome et al, 2022), building refurbishments (Pohoryles et al, 2020Napoli et al, 2020;Arbulu et al, 2021;Buckley et al, 2021;Loli & Bertolin, 2021), technology (Hainsch et al, 2021), transport (Hass & Sander, 2020, urban tourism (Popescu et al, 2022), regional development (Piontek, 2020) and economic recovery (García Vaquero et al, 2021;Kougias et al, 2021;Bongardt & Torres, 2022), etc. Building refurbishments, as a way to reduce greenhouse gas emissions and to reduce resources consumptions for heating, triggered our attention towards renovating residential flats.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study is part of the research project LOCAL-REGEN, where previous studies have been conducted on the assessment frameworks of European research and technological development (RTD) projects [3], as well as on the barriers and challenges of the MPIs within the assessment framework of the Commission Recommendation (EU) 2019/786 [2], by analysing their concordance with the evaluation framework of European RTD projects [4]. This second study found low data availability and reliability as the main barriers, along with the need to prioritize and shortlist the large amount of MPIs [4].…”
Section: Contextmentioning
confidence: 99%